Portal Annular Pancreas With Common Hepatic Artery Trajectory Abnormality: A Case Report and Review of the Literature. Issue 4 (April 2021) - Tahara, Munenori; Harada, Takuya; Wakui, Yosuke; Mizukami, Shoichiro; Kita, Kengo; Funakoshi, Tohru; Wakayama, Kenji; Ishizu, Hiroyuki
Abstract : Abstract: Portal annular pancreas (PAP) is a rare congenital pancreatic anomaly, in which the uncinate process of the pancreas fuses to the body of pancreas behind the portal vein. Here, we report a case of PAP with common hepatic arterial anomaly, which was identified during surgery. A 57-year-old man who had branch type intraductal papillary mucinous neoplasm in the head of the pancreas developed a nodule in the cystic lesion. We planned pylorus preserving pancreaticoduodenectomy. The common hepatic artery from the celiac artery passing behind the portal vein was revealed in preoperative examinations. During surgery, we discovered that the uncinate process of the pancreas was fused with the body of the pancreas behind the portal vein. We divided the pancreas at the anterior and posterior of the portal vein. The main pancreatic duct was present in the anterior pancreatic stump. We performed pancreaticojejunostomy in the anterior stump and closed the posterior stump by interrupted suture. Forty-four surgical cases of PAP have been reported in the English medical literature. There are few previous reports of PAP which involved an arterial anomaly. Clinicians should consider PAP preoperatively to ensure that the surgeon can appropriately plan pancreatic resection to avoid postoperative complications.